Comparison between Tanaka/Johnston and Boston University prediction approaches in a group of Iraqi pupils - Khawla M Awni (University of Mosul, College of Dentistry, 2005)
Abstract The purpose of this study was to compare two mixed dentition prediction methods that do not require the use of periapical radiographs of the unerupted permanent lower teeth. The two compared methods were the Tanaka/Johnston (T/J) and the Boston University (BU) prediction approaches. Study casts of 52 children (20 males and 32 females) were used; those children were selected from primary and secondary schools located in different areas of Mosul City. All subjects have normal Class I molar relationship. The finding indicated that on the average the T/J approach overestimated the tooth size of the unerupted teeth (mean + SD = 1.02 + 1.07 mm). On the other hand, the BU approach underestimated the tooth size of the unerupted teeth (mean + SD = -0.2 + 1.07 mm). The findings further indicated that there were statistically significant correlation between the predicted and actual tooth size. The error involved in the use of the prediction equations was expressed as the standard error of the estimate (SEE). The present findings indicated that the SEE for T/J prediction ranged between 0.52-0.63 mm and the corresponding values for BU equation ranged between 0.45-0.68 mm. Depending on the stage of dental development; i.e., which deciduous and permanent teeth are present, the T/J approach can be used when the only permanent four mandibular incisors have completely erupted, whereas the BU approach can be used when all the deciduous (canines and first molars) are still present.